Hatchability Success Rate of Olive Ridley Sea Turtle (Lepidochelys olivacea) Eggs Using the INTAN BOX Incubation Device on Pulau Santen Beach, Banyuwangi - Yudhana, Aditya; Sari, Jayanti Dian Eka; Praja, Ratih Novita; Herdiansyah, Akbar Dimas; Nurfaizah, Diza Ulya; Farezi, Reza Adrio; Muslimah, Bintang; Puspikawati, Septa Indra; Kenconojati, Hapsari; Soetojo, Soetojo; Susilo, Rahadian Indarto; Mufasirin, Mufasirin; Haditanojo, Wiyanto; Saksono, Bayu; Sukarno, Gerda (Journal of Basic Medical Veterinary, 2025)
The natural hatching success rate of olive ridley sea turtle (Lepidochelys olivacea) eggs on Pulau Santen Beach is often hindered by predator disturbances, temperature fluctuations caused by human activities, and unfavorable environmental conditions, with a success rate of only 50–70%. This study aimed to analyze the hatching success rate of olive ridley sea turtle eggs using the INTAN BOX incubation device on Pulau Santen Beach, Banyuwangi. A quantitative descriptive method was employed to observe 365 eggs relocated from four nests to the INTAN BOX over an incubation period of 50–60 days. Parameters observed included temperature, humidity, and hatching success rates. Results indicated an average hatching success rate of 86%, with individual nest success rates ranging from 83% to 89%. These rates are significantly higher than the 50–70% success rate achieved through natural hatching. The INTAN BOX provides a stable environment, protects eggs from predators, and optimizes temperature and humidity conditions, thereby enhancing hatching success. Additionally, the device enables the management of hatchling sex ratios through temperature-dependent sex determination (TSD), which is critical for sea turtle population conservation. This study concluded that the INTAN BOX is an effective innovation for olive ridley turtle conservation while also supporting local community empowerment around Pulau Santen Beach.